Design and Fabrication of Conformal Cooling Channels with Vacuum Diffusion Bonding - Huang, Jinchang; Lu, Yanjin; Wang, Qianting; Lin, Frank (Recent Patents on Chemical Engineering, 2013)
The cooling system is the most critical for injection mold to affecting in productivity and quality of plastic production. Traditional cooling channel is based on the conventional machining processes. It will cause long cooling time and poor cooling quality because of non-uniform cooling. This paper designed three kinds of cooling layouts for an outer housing plastic part. Simulation analysis was carried out to find the cooling effect of three kinds of cooling layouts. Considering both simulation results and mold manufacturing costs, the second cooling layouts which hybridize traditional with conformal cooling channels was fabricated by vacuum diffusion bonding. Then, outer housing plastic part was produced through injection molding. A method called cooling layouts parting method was proposed. Based on cooling layout parting method and vacuum diffusion bonding, CCC with freeform sharp can be fabricated at relatively low cost which would promote the application of plastic injection mold with CCC.
Keywords: Conformal cooling channel